Personality Traits and Marital Satisfaction in Predicting Couples' Attitudes Toward Infidelity. (2019) - Isma, Mentari Namira Pertiwi; Turnip, Sherly Saragih
Abstract: This study aims to investigate the role of marital satisfaction and personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) in predicting attitudes toward infidelity. The participants of the study were 438 married men and women ranging in age from 22 to 40 years old ( M = 31.02, SD = 4.3). The results from the NEO Five-Factor Inventory (NEO-FFI), Evaluation and Nurturing Relationship Issues, Communication and Happiness (ENRICH) Marital Satisfaction Scale and Attitudes toward Infidelity Scale used in this study indicate that conscientiousness and neuroticism, followed by marital satisfaction and gender, are significant predictors of attitudes toward infidelity. From these results, it can be concluded that attitudes toward infidelity can be predicted by demographic, interpersonal, and intrapersonal factors.